Deformation Caused by Dynamic Load and Support Requirements in a Deep Gob-Side Entry Rock Mass - Yandong Zhang; Yongjie Yang; Changhua Zhuge (Advances in Materials Science and Engineering)
Gob-side entries in deep coal mines can be subjected to dynamic loading when driving along the goaf. The effects of this dynamic loading and improved ground support requirements are investigated in the Gaojiabao Coal Mine, China. Numerical modeling is first used to simulate the deformation characteristics of rock surrounding the gob-side entry under dynamic load with the original support design. Dynamic loading in this scenario causes continual deterioration in rock properties, and deformation accumulates as the number of dynamic loads increases. Therefore, the overall strength and rigidity of the bolt support design need improvement, especially in terms of using yielding bolts that assist in releasing unnecessary support loads. The deformation characteristics of the rock surrounding the gob-side entry are combined with the concept of coupled pressure support to provide an optimized bolt support design. The support effects of the optimized design are then also numerically simulated and compared with the original support design. Deformation in the optimized design is significantly reduced, and roadway control is improved. Finally, the optimized design is applied and measured in a gob-side entry excavation. The field test results show that the potential for loosening, deformation, and failure of the surrounding rock is effectively controlled.